2017
DOI: 10.1096/fj.201700377r
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐mediated blockade of JMJD6 interaction with collagen I exerts antifibrotic and antimetastatic activities

Abstract: JMJD6 is known to localize in the nucleus, exerting histone arginine demethylase and lysyl hydroxylase activities. A novel localization of JMJD6 in the extracellular matrix, resulting from its secretion as a soluble protein, was unveiled by a new anti-JMJD6 mAb called P4E11, which was developed to identify new targets in the stroma. Recombinant JMJD6 binds with collagen type I (Coll-I), and distinct JMJD6 peptides interfere with collagen fibrillogenesis, collagen-fibronectin interaction, and adhesion of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Furthermore, JMJD6 overexpression in pMSC-derived ECM abrogated HTR-8/SVneo cell migration on the matrix, suggesting that regulation of the JMJD6-FN rheostat in pMSCs is critical for EVT cell motility. Recently, Miotti et al (2017) reported that besides its typical localization in the nucleus, JMJD6 was also secreted into the ECM deposited by human tumor cell lines where it was found to interact with collagen type I (COL-I) and influence subsequent collagen–FN interaction. Interestingly, the authors proposed that the function of JMJD6 in the ECM is independent of its JmjC domain ( Miotti et al, 2017 ), suggesting that JMJD6 may also indirectly affect FN function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, JMJD6 overexpression in pMSC-derived ECM abrogated HTR-8/SVneo cell migration on the matrix, suggesting that regulation of the JMJD6-FN rheostat in pMSCs is critical for EVT cell motility. Recently, Miotti et al (2017) reported that besides its typical localization in the nucleus, JMJD6 was also secreted into the ECM deposited by human tumor cell lines where it was found to interact with collagen type I (COL-I) and influence subsequent collagen–FN interaction. Interestingly, the authors proposed that the function of JMJD6 in the ECM is independent of its JmjC domain ( Miotti et al, 2017 ), suggesting that JMJD6 may also indirectly affect FN function.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Miotti et al (2017) reported that besides its typical localization in the nucleus, JMJD6 was also secreted into the ECM deposited by human tumor cell lines where it was found to interact with collagen type I (COL-I) and influence subsequent collagen–FN interaction. Interestingly, the authors proposed that the function of JMJD6 in the ECM is independent of its JmjC domain ( Miotti et al, 2017 ), suggesting that JMJD6 may also indirectly affect FN function. One report suggests that JMJD6 interacts with the epigenetic reader, bromodomain-containing protein 4 (BRD4) that is a potent transcriptional repressor of lysosomal function and the autophagy machinery ( Liu et al, 2013 ; Sakamaki et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 In mice injected with breast carcinoma cells, treatment with P4E11, a monoclonal antibody specific for JMJD6, can reduce fibrosis at the primary tumour and metastatic burden by blockading the interaction of JMJD6 with collagen I, which is also confirmed in xenograft mouse model of ovarian cancer. 25 In breast cancer samples from patients, the expression of JMJD6 is different in different breast cancer subtypes: JMJD6 expression in ER-positive (ER+) tumours is slightly but significantly lower than in ER-negative (ER−) tumours (JMJD6 expression is consistently associated with ER− disease); the expression of JMJD6 is highest in Claudin-low and basal subtypes followed by HER2-enriched and luminal B subtypes, and lowest in luminal A subtype. 12 In both ER+ and ER− breast cancer patients, elevated expression of JMJD6 is positively associated with histological grade, age, lymph node metastasis, tumour size and advanced tumour node metastasis (TNM).…”
Section: Breast Cancermentioning
confidence: 96%
“…Moreover, it has also been reported to be a secreted protein in the extracellular matrix (Ref. 62). JMJD6 facilitates cell proliferation and migration in vitro, and promotes tumour growth in vivo (Refs 63, 64).…”
Section: Jmjd6 Localisation and Enzymatic Activitymentioning
confidence: 99%